Novel Hemizygous IL2RG p.(Pro58Ser) Mutation Impairs IL-2 Receptor Complex Expression on Lymphocytes Causing X-Linked Combined Immunodeficiency - Tuovinen EA (SPRINGER/PLENUM PUBLISHERS, 2025)
Hypomorphic IL2RG mutations may lead to milder phenotypes than X-SCID, named variably as atypical X-SCID or X-CID. We report an 11-year-old boy with a novel c. 172C>T;p.(Pro58Ser) mutation in IL2RG, presenting with atypical X-SCID phenotype. We also review the growing number of hypomorphic IL2RG mutations causing atypical X-SCID. We studied the patient's clinical phenotype, B, T, NK, and dendritic cell phenotypes, IL2RG and CD25 cell surface expression, and IL-2 target gene expression, STAT tyrosine phosphorylation, PBMC proliferation, and blast formation in response to IL-2 stimulation, as well as protein-protein interactions of the mutated IL2RG by BioID proximity labeling. The patient suffered from recurrent upper and lower respiratory tract infections, bronchiectasis, and reactive arthritis. His total lymphocyte counts have remained normal despite skewed T and B cells subpopulations, with very low numbers of plasmacytoid dendritic cells. Surface expression of IL2RG was reduced on his lymphocytes. This led to impaired STAT tyrosine phosphorylation in response to IL-2 and IL-21, reduced expression of IL-2 target genes in patient CD4+ T cells, and reduced cell proliferation in response to IL-2 stimulation. BioID proximity labeling showed aberrant interactions between mutated IL2RG and ER/Golgi proteins causing mislocalization of the mutated IL2RG to the ER/Golgi interface. In conclusion, IL2RG p.(Pro58Ser) causes X-CID. Failure of IL2RG plasma membrane targeting may lead to atypical X-SCID. We further identified another carrier of this mutation from newborn SCID screening, lost to closer scrutiny.